Neutron skins: A perspective from dispersive optical models - Atkinson, M. C.; Dickhoff, W. H. (Frontiers in Physics, 2024)
An overview is presented of neutron skin predictions obtained using an empirical nonlocal dispersive optical model (DOM). The DOM links both scattering and bound-state experimental data through a subtracted dispersion relation which allows for fully-consistent, data-informed predictions for nuclei where such data exists. Large skins were predicted for both 48 Ca (R 48 skin = 0.25 ± 0.023 fm in 2017) and 208 Pb (R 208 skin = 0.25 ± 0.05 fm in 2020). While the DOM prediction in 208 Pb is within 1σ of the subsequent PREX-2 measurement, the DOM prediction in 48 Ca is over 2σ larger than the thin neutron skin resulting from CREX. From the moment it was revealed, the thin skin in 48 Ca has puzzled the nuclear-physics community as no adequate theories simultaneously predict both a large skin in 208 Pb and a small skin in 48 Ca. The DOM is unique in its ability to treat both structure and reaction data on the same footing, providing a unique perspective on this R skin puzzle. It appears vital that more neutron data be measured in both the scattering and bound-state domain for 48 Ca to clarify the situation.